La propiocepción en el desarrollo del dribling en jugadores de baloncesto en categoría infantil - Ortega Suarez, Jhayr Alonso (2025)
The main objective of this research was to analyze the influence of a proprioceptive training program on the development of dribbling in children's category basketball players. The study originated from a problem detected at the "Jhayro’s" Specialized Formative Basketball Club in Riobamba. Athletes there showed difficulties in fluency, control, and security when handling the ball. The methodology used a mixed-methods approach and a single-group quasi-experimental pretest-posttest design. The non-probabilistic convenience sample included 10 players in the children's category (ages 12-13). Data was collected through structured observation, using a Dribbling Test to measure performance before and after a 12-week intervention. The training program included progressive exercises to improve balance and body awareness on stable and unstable surfaces. The results showed significant improvement. In the initial evaluation (pretest), 50% of players were at a "Regular" level. After the program (posttest), 80% reached the "Good" category, "Regular" results dropped to 20%, and the "Deficient" category stayed at 0%. It is concluded that proprioception-focused training is an effective methodological strategy. It directly and positively influences ball control, stability, and dribbling fluency in young athletes